An Appraisal Analysis of Attitude in Dr. W.C. Minor and Prof. James Murray’s Utterances in The Professor and the Madman (2019) Movie - Novia Setyana Khusnul Khotimah; Widhiyanto (Institut Agama Islam Negeri Palopo, 2025)
This study is a discourse study which was conducted to find out the appraisal analysis through Attitudes from James Murray and W.C. Minor, the main character in The Professor and the Madman movie. The study examined the features of the three types of attitudes: affect, judgement and appreciation using Murray and Minor Minor’s utterances as the main data. The analysis focused on clauses, which were segmented from the characters’ utterances. These clauses were examined and interpreted using Halliday’s (1994) framework of interpersonal meaning within the Systemic Functional Grammar (SFG) approach. SFG views language as a resource of meaning making, and interpersonal meaning is one of the meanings of language which shows the role relationship between interlocutors. The analysis revealed that Murray employed more attitude resources of judgement, whereas Minor used more attitude resources of affect. The findings also revealed that each of the two characters presented the attitude types and polarity that shows their characteristics and the background issues underlining it. Finally, the findings indicate that the overall atmosphere of the per scenes in the movie was highly affected by the attitudinal exchanges between the characters and their respective background issues.